2014
DOI: 10.3176/oil.2014.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Kerogen Transformation During Pyrolysis by Applying a Diamond Anvil Cell

Abstract: Pyrolysis of Bulgarian oil shale was studied by using a diamond anvil cell, which allows one to observe directly the conversion of organic matter to mobile oily liquid, solid residue and gas. This method gives the possibility to detect very precisely the temperatures of kerogen transformation during pyrolysis. It was observed that most of the gaseous products were generated later than oily liquids, most probably by cracking processes of liquid products. Due to the strong connection between mineral and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The ability of solid kerogen to undergo shrinkage was detected by Budinova et al [66] and Saad Alafnan [67]. Budinova et al found that solid kerogen could flow during heating even at low temperatures.…”
Section: Kerogen Microstructural Transformationmentioning
confidence: 96%
See 1 more Smart Citation
“…The ability of solid kerogen to undergo shrinkage was detected by Budinova et al [66] and Saad Alafnan [67]. Budinova et al found that solid kerogen could flow during heating even at low temperatures.…”
Section: Kerogen Microstructural Transformationmentioning
confidence: 96%
“…Budinova et al found that solid kerogen could flow during heating even at low temperatures. Kerogen samples were heated in an open system in a pyrolizer with an intercepted diamond anvil cell, and the squeezing and flow of studding matter were detected at temperatures lower than 160 • C [66]. Saad Alafnan studied the mechanical properties of kerogen, and identified that, as the temperature increased, kerogen underwent prolonged plastic deformation before failure.…”
Section: Kerogen Microstructural Transformationmentioning
confidence: 99%